MONO- AND POLYCRYST SILICON JUSTIFIED THE SUN SIMPLE OPERATION OF THE ELEMENTS TO VOLTAGE LIGHT INTENSITY INFLUENCE SINTON SUNS- VOC DEVICE USING DETERMINATION (Academicia Globe: Inderscience Research, 2023)
This article describes the determination of the effect of light intensity on the operating voltage of mono- and polycrystalline silicon-based solar cells using the Sinton Suns-Voc device.